X Weltfestspiele der Jugend und Studenten : Berlin, 1973 - Bertram, Axel (1973)
Symbol of globe as centre of a flower, with colourful petals surrounding it Poster advertising X world festival of youth and students, held in Berlin, 1973 PO-1594